2021
DOI: 10.1016/j.jbi.2021.103787
|View full text |Cite
|
Sign up to set email alerts
|

Can technological advancements help to alleviate COVID-19 pandemic? a review

Abstract: The COVID-19 pandemic is continuing, and the innovative and efficient contributions of the emerging modern technologies to the pandemic responses are too early and cannot be completely quantified at this moment. Digital technologies are not a final solution but are the tools that facilitate a quick and effective pandemic response. In accordance, mobile applications, robots and drones, social media platforms (such as search engines, Twitter, and Facebook), television, and associated technologies deployed in tac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 95 publications
0
27
0
Order By: Relevance
“…As a rule of thumb, a magnitude no less than 0.25 has been proposed to be an average score, whereas a magnitude below 0.13 is insufficient to pass this criterion in the behavioral sciences. In contrast, the badness of outcome is exhibited by any score less than or equal to 0.03 [ 48 ]. In the present case, the R-square value is 0.807, which is well above 0.25, satisfying the path model’s first criterion ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a rule of thumb, a magnitude no less than 0.25 has been proposed to be an average score, whereas a magnitude below 0.13 is insufficient to pass this criterion in the behavioral sciences. In contrast, the badness of outcome is exhibited by any score less than or equal to 0.03 [ 48 ]. In the present case, the R-square value is 0.807, which is well above 0.25, satisfying the path model’s first criterion ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intawong et al [ 47 ] studied the role of application technology in Thailand in helping the COVID-19 patients and high-risk individuals to discover their disease symptoms through quick tracking strategies. In another work, Thomas et al [ 48 ] assessed the role of technologies in facilitating the prevention of pandemics worldwide. To this end, social media, artificial intelligence, and other digital technologies helped to promote the ease of pandemic prevention.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…For instance, drones equipped with autonomous thermal cameras and face recognition software may pose privacy issues such as over surveillance [71] . Personal data collected with Unmanned Aerial vehicles (UAVs) or drones can lead to a privacy breach [72] .…”
Section: Results Analysismentioning
confidence: 99%
“…Several countries have found that new technologies, such as mobile applications, robots, and drones, can minimize human contact. Communicated diseases, such as influenza, herpes, or Ebola, are being held at bay by systems such as teleoperation, autonomous service robots, face recognition, and thermal scanning [2]. According to experts, future robots that are not susceptible to infection and that can be effectively disinfected will be highly important in the struggle against the next pandemic [1].…”
Section: Introductionmentioning
confidence: 99%
“…One can think of security robots, restaurant cooking robots, robot luggage handlers, travel agents, and receptionists, or concierge robots, as examples of this concept [10]. Because these drones are rugged and flexible, they are frequently used in various industries, such as travel, healthcare, disinfection, and logistics, for screening and monitoring in order to minimize the likelihood of a resurgence of the infection known as COVID-19 [2].…”
Section: Introductionmentioning
confidence: 99%